Governabilitas Pemerintah Desa Rantau Panjang Dalam Pengembangan Budaya Lokal Dayak Kenyah - Very Saputra; Yuli Setyowati (CV. Ulil Albab Corp, 2024)
This research examines the Governability of the Rantau Panjang Village Government in the Development of Local Dayak Kenyah Culture (Study in Rantau Panjang Village, Telen District, East Kutai Regency, East Kalimantan Province). The aim of this research is to examine and describe the governance of the Rantau Panjang Village government in developing local Dayak Kenyah culture and to determine the driving and inhibiting factors in the development of local Dayak Kenyah culture. This type of research is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation, as well as data triangulation to assess the credibility of data obtained from the same sources but using different techniques. The results of research on village government governance in developing local culture are: The development of local Dayak Kenyah culture in Rantau Panjang Village can be seen from three aspects: communication, coordination and program continuity. First, communication between the village government and indigenous communities has the same vision and perspective regarding advancing local culture, this is a similarity because there is good communication between both parties, which will support the Dayak Kenyah local cultural development program in Rantau Panjang Village. Second, the village government pays little attention to cultural facilities, coordination between indigenous communities and the village government is not effective and optimal. As a result, community efforts to develop local culture, such as carving traditional lamin, failed. Third, the village government has tried to develop local culture through training, such as making Dayak Kenyah carvings, but community participation in the training s very low. The development of local Dayak Kenyah culture in Rantau Panjang Village is encouraged and inhibited by internal and external factors. First, the driving factors for local cultural development consist of the village government and the Dayak Kenyah indigenous community of Rantau Panjang Village, while external factors consist of human resources, infrastructure and facilities. Second, the factors inhibiting the development of local culture are internal and external factors. Internal factors include lack of good coordination, lack of clarity and unsustainability of the program and personal sentiment. The external factors are low community participation and lack of market access.